2014
DOI: 10.3390/ijms15057787
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dioxin and Other Persistent Organic Pollutants (POPs) with Diabetes: Epidemiological Evidence and New Mechanisms of Beta Cell Dysfunction

Abstract: The worldwide explosion of the rates of diabetes and other metabolic diseases in the last few decades cannot be fully explained only by changes in the prevalence of classical lifestyle-related risk factors, such as physical inactivity and poor diet. For this reason, it has been recently proposed that other “nontraditional” risk factors could contribute to the diabetes epidemics. In particular, an increasing number of reports indicate that chronic exposure to and accumulation of a low concentration of environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 216 publications
0
22
0
1
Order By: Relevance
“…Further, it is not clear whether toxicant-associated steatohepatitis develops in humans exposed to TCDD [104] and although there appears to be an association between dioxin and type 2 diabetes a causal link is not necessarily implied [5,10,105,106]. Continued investigation in a variety of model systems clearly seems warranted to further elucidate the mechanisms of action of these pollutants in humans.…”
Section: Discussionmentioning
confidence: 87%
“…Further, it is not clear whether toxicant-associated steatohepatitis develops in humans exposed to TCDD [104] and although there appears to be an association between dioxin and type 2 diabetes a causal link is not necessarily implied [5,10,105,106]. Continued investigation in a variety of model systems clearly seems warranted to further elucidate the mechanisms of action of these pollutants in humans.…”
Section: Discussionmentioning
confidence: 87%
“…Possible biologic pathways through which POPs could affect diabetes incidence have been hypothesized, including insulin resistance (Kern et al 2004), pancreatic beta cell destruction (De Tata 2014), mitochondrial dysfunction (Lee 2011), alterations in steroid metabolism (Persky et al 2011;Persky et al 2012), antagonism of PPARγ expression (Remillard and Bunce 2002), and induction of low grade chronic inflammation (Fujiyoshi et al 2006), oxidative stress (Lee et al 2008), and autoimmunity (Langer et al 2002). This study explored some of these potential pathways using biomarkers of diabetes risk.…”
Section: Introductionmentioning
confidence: 99%
“…Research strongly implicates Beta-cell mitochondrial dysfunction in the pathogenies of type 2 diabetes [105,106]. Research shows an association between POPs and mitochondrial dysfunction in the Beta cells [104][105][106][107]. One study showed a strong association, with a dose-response relationship with organochlorine POPs and diabetic peripheral neuropathy.…”
Section: The Impact Of Pop Exposure On Laboratory Animalsmentioning
confidence: 99%
“…Adipose tissue is a common site of POPs accumulation where they can induce adverse effects on human health [104]. Research strongly implicates Beta-cell mitochondrial dysfunction in the pathogenies of type 2 diabetes [105,106].…”
Section: The Impact Of Pop Exposure On Laboratory Animalsmentioning
confidence: 99%